Two-write WOM-codes for non-volatile memories - Chua, Melissa Wan Jun (2013)
A Write Once Memory (WOM) is defined as a class of storage medium with each storage element, known as a cell, containing binary information. In the context of a WOM, there is an added constraint, whereby the cells can only move irreversibly from the zero state to the one state. In this work, we investigate the problem of rewriting WOM for two successive writing operations, since having a higher number of writing operations would require a larger decrease of the code rate and hence the memory storage efficiency. We first analyze a two-write WOM-Code construction method and then propose a criterion to select a linear code such that the WOM-Rate is maximized. By using the proposed criterion, we design efficient WOM-Codes, whose rates are higher than those available in literature.